Engagement strategy for customer loyalty in a Peruvian Company (LACCEI, 2024)
The general objective of this research was to identify how the engagement strategy affects customer loyalty of Econolentes, Metropolitan Lima 2021. In this sense, a nonexperimental, cross-sectional design was used, with a quantitative and explanatory level approach. The population under study was infinite, made up of clients over 18 years of age who interact with the company in person, online or both. We worked with a nonprobabilistic sample for convenience, made up of 150 clients. The technique used was the survey. The instrument used to measure the variables was the Likert-type ordinal scale questionnaire, which obtained a Cronbach's alpha of 0.94, which means excellent statistical reliability. and a content validation of 89% by experts. Overall, it is concluded that the Engagement Strategy has a 68.3% impact on customer loyalty of the company Econolentes, Metropolitan Lima 2021, identified through regression analysis, with a significance level of 0.000 and a correlation coefficient of 0.827, which indicates that applying Engagement Strategies is beneficial to ensure customer continuity.